2013
DOI: 10.1111/jsm.12024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Energy Shockwave Therapy on the Erectile Function and Tissue of a Diabetic Rat Model

Abstract: Introduction Low-energy shockwave therapy (LESWT) has been shown to improve erectile function in patients suffering from diabetes mellitus (DM)-associated erectile dysfunction (ED). However, the underlying mechanism remains unknown. Aim To investigate whether LESWT can ameliorate DM-associated ED in a rat model, and examine the associated changes in the erectile tissues. Methods Newborn male rats were intraperitoneally injected with 5-ethynyl-2-deoxyuridine (EdU, 50mg/kg) for the purpose of tracking endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 29 publications
3
126
0
7
Order By: Relevance
“…It was thus shown that Li-ESWT triggers the activation of various intracellular signaling pathways causing upregulation of numerous angiogenic factors (i.e., VEGF…) to promote neovascularization and mobilizes the recruitment of endogenous progenitor cells thereby favoring angiogenesis and tissue regeneration in cardiovascular medicine and wound healing (17)(18)(19)(20)(21). These pro-angiogenic signaling pathways and recruitment of endogenous progenitor cells have also been shown to be activated in the penile tissue following Li-ESWT treatment in diabetic ED models (15,16), despite the fact that it does not upregulate the NO/cGMP pathway (14). Moreover, the role of Li-ESWT in the regeneration of peripheral nerves has also been previously suggested after nerve compression or in a model of autologous nerve graft (22,23) and later investigated in the context of erectile function recovery in diabetic ED models (15,16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was thus shown that Li-ESWT triggers the activation of various intracellular signaling pathways causing upregulation of numerous angiogenic factors (i.e., VEGF…) to promote neovascularization and mobilizes the recruitment of endogenous progenitor cells thereby favoring angiogenesis and tissue regeneration in cardiovascular medicine and wound healing (17)(18)(19)(20)(21). These pro-angiogenic signaling pathways and recruitment of endogenous progenitor cells have also been shown to be activated in the penile tissue following Li-ESWT treatment in diabetic ED models (15,16), despite the fact that it does not upregulate the NO/cGMP pathway (14). Moreover, the role of Li-ESWT in the regeneration of peripheral nerves has also been previously suggested after nerve compression or in a model of autologous nerve graft (22,23) and later investigated in the context of erectile function recovery in diabetic ED models (15,16).…”
mentioning
confidence: 99%
“…These pro-angiogenic signaling pathways and recruitment of endogenous progenitor cells have also been shown to be activated in the penile tissue following Li-ESWT treatment in diabetic ED models (15,16), despite the fact that it does not upregulate the NO/cGMP pathway (14). Moreover, the role of Li-ESWT in the regeneration of peripheral nerves has also been previously suggested after nerve compression or in a model of autologous nerve graft (22,23) and later investigated in the context of erectile function recovery in diabetic ED models (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estos medicamentos son efectivos antes del acto sexual, pero no logran mejorar las erecciones espontáneas y su efecto es esencialmente limitado en el tiempo (7,24). Hasta 30% de los pacientes presentan efectos adversos de moderados a graves o tienen contraindicaciones para la toma de estos medicamentos, entre ellas, los intolerantes a los efectos secundarios (cefalea principalmente) y los que toman nitratos para la angina de pecho (25,26).…”
Section: Tratamientounclassified
“…Los resultados invariablemente apuntan a la inducción de la angiogénesis como uno de los mecanismos subyacentes a los efectos de la terapia con estas ondas. Además, uno de estos estudios también identificó como un posible mecanismo el reclutamiento de células madre mesenquimales (25,43). Nishida y colaboradores (44) propusieron un modelo porcino de disfunción miocárdica inducida por isquemia y encontraron que la terapia con ondas de choque de baja intensidad regula la expresión del VEGF en el miocardio isquémico y mejora el flujo sanguíneo miocárdico regional y la fracción de eyección ventricular izquierda, lo que podría explicar los resultados obtenidos en la DE.…”
Section: Ondas De Choque En El Tratamiento De La Disfunción Eréctilunclassified